Succession Patterns and Physical Niche Partitioning in Microbial Communities from Subsurface Coal Seams - Vick, Silas H.W.; Greenfield, Paul; Pinetown, Kaydy L.; Sherwood, Neil; Gong, Se; Tetu, Sasha G.; Midgley, David J.; Paulsen, Ian T. (iScience, 2019)
The subsurface represents a largely unexplored frontier in microbiology. Here, coal seams present something of an oasis for microbial life, providing moisture, warmth, and abundant fossilized organic material. Microbes in coal seams are thought to syntrophically mobilize fossilized carbon from the geosphere to the biosphere. Despite the environmental and economic importance of this process, little is known about the microbial ecology of coal seams. In the current study, ecological succession and spatial niche partitioning are explored in three coal seam microbial communities. Scanning electron microscopic visualization and 16S rRNA sequencing track changes in microbial communities over time, revealing distinct attached and planktonic communities displaying patterns of ecological succession. Attachment to the coal surface is biofilm mediated on Surat coal, whereas microbes on Sydney and Gunnedah coal show different attachment processes. This study demonstrates that coal seam microbial communities undergo spatial niche partitioning during periods of succession as microbes colonize coal environments.